DIRK : an experimental participatory recycling process. - Oldershaw, Catherine; Kraus, Katharina Sofie; Morillon, Guillaume (Kortrijk : Designregio Kortrijk, 2016)
Oldershaw, Catherine ; Morillon, Guillaume ; Kraus, Katharina Sofie
Designers in Residence Kortrijk 2016
boek